Impacts of the shape of soft nanochannels on their ion selectivity and current rectification. (10th December 2021) - Karimzadeh, Mohammad; Seifollahi, Zahra; Khatibi, Mahdi; Ashrafizadeh, Seyed Nezameddin
Highlights: The effects of the nanochannel geometry on the electroosmotic flow and electrokinetic phenomena are studied. The selectivity and rectification behavior of soft nanochannels are investigated. Differences in symmetric and asymmetric geometries of nanochannels in rectifying the ionic currents are demonstrated. The effect of ionic partitioning effect on the selectivity of nanochannels is identified. Ion selectivity and rectification were improved by considering the ionic partitioning effect. Abstract: The influence of channel geometry on the ion selectivity and ionic current rectification (ICR) of soft nanochannels was numerically investigated. The nanochannels coated with polyelectrolyte layers (PELs) are termed as soft nanochannels. Two categories of channels, asymmetric (trumpet, conical, bullet, and cigar-like) and symmetric (cylindrical), were considered in this study. When PEL is dense, the ionic partitioning effect can not be ignored. To this end, through adopting a numerical approach using the finite element method (FEM), Poisson-Nernst-Planck and Navier-Stokes equations were solved at steady-state conditions by considering different values of permittivity, diffusivity, and dynamic viscosity for the PEL and the electrolyte. The model findings were verified by comparing them with the existing simulation data. For the cylindrical type nanochannels, the results indicate that the rectification factor is approximately equal to unity, and the ion selectivity at positive voltages is approximately equal to that at negative voltages. For other geometries, the ion selectivity factor of the channel was S Trumpet > S Conical > S Bullet > S Cigar . On the other hand, at low bulk concentrations, the rectification factor was R f Cigar > R f Bullet > R f Conical > R f Trumpet, while at high bulk concentrations, it was R f Bullet > R f Cigar > R f Conical > R f Trumpet . Considering a charge density of 80 mol / m 3 and a bulk concentration of 20 mM, we demonstrate that the rectification factors for the bullet and trumpet types nanochannels, from 3.35 and 0.56 by ignoring the ion partitioning effect, can reach the values of 5.78 and 0.83 by considering the ion partitioning effect, respectively. Graphical abstract: Image, graphical abstract